Panama : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper assesses risks in the Panamanian banking sector. The analysis suggests that Panama's banking system seems able to withstand reasonably severe shocks, while contagion risks stem primarily from foreign banks. Ample starting capital buffers and bank profitability prevent translation of higher loan defaults under stress into materially impair capital adequacy ratios. Reverse engineering the exercise to gauge what it would take to erase one-fourth of system capital reveals that the shock would need to be not only unprecedented, but also extremely large. In terms of contagion, while failures of both domestic and foreign banks would result in significant capital losses for Panamanian banks, the risk of contagion propagation is much higher in the case of the latter.